Integrating Lean Manufacturing and Facility Layout Optimization to Reduce Transportation Waste in Tempeh Production - Tiaradia Ihsan; Rendiyatna Ferdian; Mila Oktaviani (Industrial and Domestic Waste Management, 2026)
This study aimed to reduce transportation waste in tempeh production by integrating Lean Manufacturing tools with facility layout optimization and to evaluate the resulting operational and economic improvements. The study employed a descriptive quantitative case study conducted at a traditional tempeh production facility in Bandung, Indonesia. Waste identification was carried out using the Seven Waste framework and was prioritized using the Borda Count method. Lean tool selection was guided by the Value Stream Analysis Tool (VALSAT). Process analysis was conducted using Value Stream Mapping (VSM), Process Activity Mapping (PAM), and Root Cause Analysis (RCA). Facility layout optimization was performed using the Systematic Layout Planning framework, supported by Activity Relationship Charts and the Blocplan algorithm. Improvement effectiveness was evaluated using Future Process Activity Mapping (FPAM), Future Value Stream Mapping (FVSM), and Operator Material Handling (OMH) cost analysis. The results showed that transportation waste was the dominant inefficiency in the production system. The layout redesign reduced transportation time by approximately 57% and total material handling distance by 19%, while value-added processing time remained unchanged. These improvements generated measurable cost savings based on the OMH metric.